PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN PROFITABILITAS TERHADAP MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2012)
This research is a test and analyze the influence of institutional ownership, managerial ownership, leverage independent commissioner, and the profitability of earnings management in a manufacturing company that went public in Indonesia. The population in this study is a company engaged in the manufacturing sector are listed in Indonesia Stock Exchange (BEI) in 2008-2010. Sampling technique using a purposive sampling technique. According to established criteria there were 26 samples of analytical technique used is multiple regression. The results suggest that Leverage and Profitability has a positive effect on earnings management. As for institutional Ownership. Managerial ownership and The proportion of independent board of management had no effect on earnings management.Keywords: institutional ownership, managerial ownership, leverage independent commissioner, profitability and earnings management